Sacrifices in the Ancient World: Research on Complex Rituals - Schörner, Günther (The Palgrave handbook of anthropological ritual studies, 2021)
First, a brief overview of research in recent decades on sacrifice in the Greek and Roman periods is given, with a particular focus on the move away from "grand theories" toward new definitions and emic approaches. Current studies on sacrifice are also characterized by the increasing consideration not only of written sources but also of material (archaeological, zooarchaeological) and iconographic evidence. Finally, from the perspective of a classical archaeologist, an attempt is made to show how anthropological research approaches can be applied to the study of Greek and Roman rituals.